Mungkinkah Penerapan Pajak Minuman dengan Kandungan Gula di Indonesia? Studi Literatur dari Inggris dan Meksiko - Fandy Abdi Darma (Journal of Management and Social Sciences, 2025)
The sugar tax has emerged as a strategy adopted by various countries to address public health issues caused by excessive sugar consumption. This study examines the impact of the tax in the UK and Mexico, as well as its implications for Indonesia. Data from the Central Statistics Agency (BPS) show that per capita sugar consumption in Indonesia far exceeds the recommended limits set by the Ministry of Health and WHO, increasing the risk of non-communicable diseases such as diabetes and obesity. In the UK, the sugar tax successfully reduced sugar consumption, particularly among children and adolescents, while in Mexico, sugary beverage consumption also declined significantly. Besides reducing sugar intake, the tax generates revenue that can fund public health programs. However, resistance from the food and beverage industry and local communities presents challenges. This study recommends implementing a sugar tax in Indonesia as a strategic step to improve public health, supported by complementary policies promoting healthy eating and stronger consumer protections.